Pengembangan E-Modul Berbasis Kontekstual pada Materi Sistem Persamaan Linear Tiga Variabel (SPLTV) Siswa Kelas X SMA - Putri Ajeng Chia; Dodik Mulyono; Anna Fauziah (Jurnal Pendidikan Matematika : Judika Education, 2023)
This study intends to generate teaching materials for a system of three-variable linear equations in the form of E-Module mathematics material utilizing a contextual approach that is valid, useful, and may have an impact on student learning results. The ADDIE model is being used in this study approach, which is research and development (R & D). Five stages make up the ADDIE model: analysis, design, development, implementation, and evaluation. The study's findings indicate that (1) the quality of the E-Module teaching materials as perceived from the aspect of language validity is included in the very valid category with a score of 1.00, the aspect of media validity is included in the very valid category with a score of 0.82, and the aspect of material validity is included in the category very valid with a score of 1.00; (2) the quality of the E-Module teaching materials as perceived from the practicality aspect of one-to-one instruction is included in the The contextually based E-Module that was created was declared to be valid, usable, and to have good prospective impacts in addition to being engaging for students. Keywords: Contextual, SPLTV E-Module Development